PROHIBITION OF TRANSACTIONS ON THE TIKTOK SHOP E-COMMERCE BASED ON THE MINISTER OF TRADE REGULATION NO. 31 - CHRISTOFEL L. G. H. M SAMOSIR; Sunarmi; Robert (Academic Solution Publisher, 2025)
The rapid development of e-commerce in Indonesia, particularly through platforms like TikTok Shop, has brought various conveniences to buying and selling transactions, especially for Micro, Small, and Medium Enterprises (MSMEs). However, this progress has also led to various legal issues, such as a lack of oversight, consumer rights violations, and unhealthy business competition practices. The government responded by prohibiting direct transactions on social media platforms like TikTok Shop and mandating a separation between social media and e-commerce functions. This research employs a normative juridical method with a statutory and analytical approach to examine e-commerce legal regulations, the impact of the prohibition, and the adjustments made by TikTok Shop. Data was obtained from primary, secondary, and tertiary legal materials. The research findings indicate that the prohibition of direct transactions on TikTok Shop has had a significant impact on MSMEs and consumer spending patterns. Although this regulation strengthens consumer protection and legal order in digital transactions, businesses face challenges in adapting to the changes. TikTok Shop itself has made various adjustments, such as seller verification and compliance education regarding the regulations. The government continues to conduct socialization and provide assistance to MSMEs in navigating regulatory changes. Furthermore, TikTok Shop and other platforms need to build more transparent and legally compliant systems to support a healthy, fair, and sustainable e-commerce ecosystem.